Disinheritance of Women Under Esan Customary law in Nigeria: The Need for a Paradigm Shift Towards Gender Equality. - Itua, Paul (Advances in Social Sciences Research Journal, 2021)
Legal scholars, and activist in recent times had continued to advocate for equal rights of children irrespective of their gender on issues of succession or inheritance rights. The problem with gender-based discrimination are more palpable when a deceased die intestate and the principles of native law and custom regulating succession to the deceased intestate estate are fully activated. Most often, statistics have shown that female gender are discriminated against in most of the communities in Nigeria. Female children suffer the same fate under Esan customary law, because of the application of the rule of primogeniture that regulate inheritance and succession. Widows’ also are not excluded from discriminatory practises. This article seeks to examine critically the disinheritance of women either as daughters or as a widow under Esan customary law and advocate for a paradigm shift to bring its application in tandem with the Constitution. KEYWORD. Succession under Esan Customary Law, the Rule of Primogeniture and disinheritance of women.